Effect of mobility model and packet size on throughput in MANET's - Hakak, Saqib Iqbal; Abd Latif, Suhaimi; Anwar, Farhat; Alam, Mohammed Khorshed; Gilkar, Gulshan (IEEE, 2014)
Ad-hoc mobile/802.11 networks are those networks which has got no fixed topology due to the movement of end nodes. Each node within mobile adhoc network can act both host as well as router. For these mobile nodes to be properly functional and operational, routing protocol is required. And for this very purpose, studies have been going on, which protocol is better. Little emphasis has been laid on network Performance indicators as which factors are most important for a specific Performance indicator. To the best of our knowledge no one has studied effect of different factors on network performance indicators like throughput, Delay and so on, as how much influence a particular factor or group of factors is having on network performance indicators itself Thus, in this paper, effect of routing protocol, packet size and node mobility pause time have been evaluated against one of the most important network performance metric i.e. Throughput.